Implementasi Supervisi Akademik Kepala Sekolah di SMA Negeri 5 Kota Sukabumi - Suharyanto H. Soro; Sri Handayani; Budi Setia Baskara; Dian Anggraeni (Departement of Mathematics Education, 2022)
In this study, the aim was to find out how the implementation of the school principal's academic supervision at SMA Negeri 5 Sukabumi City and the type of research to be carried out was descriptive qualitative research, the subject of this study was the principal at SMA Negeri 5 Sukabumi City. While the object is the implementation of academic supervision at SMA Negeri 5 Sukabumi City. Research data was collected using observation, interview and documentation techniques. The number of informants in this study consisted of 2 people, namely the first school principal, the two teachers at SMA Negeri 5 Kota Sukabumi. The data from the research that has been carried out is that the implementation of the principal's academic supervision is not optimal but is good enough. Planning, techniques and evaluation of academic supervision carried out by the principal of SMA Negeri 5 Sukabumi City have been well structured in accordance with existing provisions, namely planning supervision The academic principal of SMA Negeri 5 Sukabumi City is carried out by meeting in advance and planning the agenda for all teachers to complete the administration before entering the starting date of the teaching and learning process at the beginning of the year, the administration is like learning tools in the form of lesson plans, lesson plans, KKM, student attendance and also includes questions that will be given to students and all documents that will be carried out or made by a teacher in preparing for a new school year or in preparing the learning process at SMA Negeri 5 Sukabumi City. the supervision technique used by the head of SMA Negeri 5 Sukabumi City, namely individually and evaluating academic supervision carried out by the principal of SMA Negeri 5 Sukabumi City in developing teacher professionalism through assessments carried out on teachers to find out how far the improvement in teacher performance has been going whether it is better or not yet.